An Overview of Farm Investigation Findings Associated with Outbreaks of Shiga Toxin-Producing Escherichia coli Infections Linked to Leafy Greens: 2009–2021 - Stelios Viazis; Michael C. Bazaco; Tyann Blessington; Sharon L. Seelman Federman; Meredith Lindsay; Travis Minor; Brittany Nork; Mia C. Mattioli; Katherine E. Marshall; Matthew E. Wise; Brett Weed; Julie Haendiges; et al. (Journal of Food Protection)
Leafy greens are a reoccurring source of Shiga toxin-producing Escherichia coli (STEC) outbreaks. We summarize data from farm investigations following STEC outbreaks linked to leafy greens conducted by the Food and Drug Administration (FDA), Centers for Disease Control and Prevention (CDC), and state and local partners, during 2009–2021. Investigational and laboratory data on multistate STEC outbreaks linked to leafy greens were collected during 2009–2021 from CDC’s Foodborne Disease Outbreak Surveillance System and FDA’s Coordinated Outbreak Response & Evaluation Network. Farm investigation information was retrieved from the FDA Farm Investigation Questionnaires and Investigation Memos. During 2009–2021, there were 49 leafy greens STEC outbreaks; 37 were linked to a specific type of leafy green. Traceback investigations were conducted for 25, and farm investigations for 17. Seven outbreaks were traced back to a single farm, and 10 were traced back to multiple farms. Environmental samples collected per investigation increased over time, and farm investigations since 2018 included a more diverse collection of environmental sample types. This overview includes a summary of the results obtained from the samples collected, including leafy greens, air, water, sediment, animal feces, and soil. The outbreak strain was identified in 6 of 17 investigations by genomic analysis, though sample and testing methods changed over time, increasing the sensitivity for pathogen detection. Collaboration between investigative partners improved the collection of samples and data through contributions from a diverse set of experts and identified possible contamination sources. Improved traceability in the supply chain can help identify single farms for investigations and focused product actions; continued grower outreach and education and adoption of regulations and best practices can help improve leafy green safety; and research to address food safety gaps can help minimize the impact of future outbreaks.